IL‐6 Activates PI3K and PKCζ Signaling and Determines Cardiac Differentiation in Rat Embryonic H9c2 Cells. Issue 3 (March 2016) - D'amico, Maria Angela; Ghinassi, Barbara; Izzicupo, Pascal; Di Ruscio, Annalisa; Di Baldassarre, Angela
Abstract : Introduction: IL‐6 influences several biological processes, including cardiac stem cell and cardiomyocyte physiology. Although JAK‐STAT3 activation is the defining feature of IL‐6 signaling, signaling molecules such as PI3K, PKCs, and ERK1/2 are also activated and elicit different responses. Moreover, most studies on the specific role of these signaling molecules focus on the adult heart, and few studies are available on the biological effects evoked by IL‐6 in embryonic cardiomyocytes. Aim: The aim of this study was to clarify the biological response of embryonic heart derived cells to IL‐6 by analyzing the morphological modifications and the signaling cascades evoked by the cytokine in H9c2 cells. Results: IL‐6 stimulation determined the terminal differentiation of H9c2 cells, as evidenced by the increased expression of cardiac transcription factors (NKX2.5 and GATA4), structural proteins (α‐myosin heavy chain and cardiac Troponin T) and the gap junction protein Connexin 43. This process was mediated by the rapid modulation of PI3K, Akt, PTEN, and PKCζ phosphorylation levels. PI3K recruitment was an upstream event in the signaling cascade and when PI3K was inhibited, IL‐6 failed to modify PKCζ, PTEN, and Akt phosphorylation. Blocking PKCζ activity affected only PTEN and Akt. Finally, the overexpression of a constitutively active form of PKCζ in H9c2 cells largely mimicked the morphological and molecular effects evoked by IL‐6. Conclusions: This study demonstrated that IL‐6 induces the cardiac differentiation of H9c2 embryonic cells though a signaling cascade that involves PI3K, PTEN, and PKCζ activities. J. Cell. Physiol. 231: 576–586, 2016. © 2015 Wiley Periodicals, Inc.